Effect of the Flavor and Quality of Wolfberry Tea Processed with Buds and Leaves under Different Degree of Spreading - Guanjun PAN; Linyuan DUAN; Jiake ZHAO; Ping SHUAI; Guoli DAI; Weisu TIAN; Jinyuan WANG; Jiapeng HUANG; Xiaotong BI; Enzhao LIN; Ken QIN; Zhilong HAO; et al. (Shipin gongye ke-ji)
This study investigated the effect of different degrees of spreading on the flavor and quality of wolfberry tea processed with buds and leaves. D and G wolfberry plants were used as the experimental materials. The sensory evaluation, flavonoids, water extracts, amino acid components, sugar substances, organic acids, and volatile substances of wolfberry tea processed with varying degrees of spreading were analyzed. The results indicated that wolfberry tea processed with D and G plants spread to 55% water content (D55%、G55%) achieved higher sensory quality scores compared to those processed with 50% and 60% water content (D50%, D60%, G50%, G60%). Overall, wolfberry tea processed with D plant spread to 55% water content exhibited floral, fruity, and sweet aromas, with a sweet and mellow taste. Similarly, tea processed with G plant spread to 55% water content showed floral and fruity aromas, with a slightly sweet aroma and a mellow, sweet taste. Compared to the tea samples processed from buds and leaves spread at 50% and 60% moisture content, the spread degree of 55% moisture content was found to be favorable for the accumulation of water extracts, amino acids, carbohydrates, and fatty acids. Meanwhile, the levels of flavonoids, water-soluble dicarboxylic acid, and hydroxyl polycarboxylic acids in the tea were decreased, while the accumulation of pleasant aroma compounds such as dihydroactinolactone was enhanced. In conclusion, both D and G plants are suitable for processing tea with a 55% water content spreading degree, providing valuable insights for the quality improvement of wolfberry tea.